Electrowetting on mineral and rock surfaces - Francisca, Franco Matias (2008)
Electrowetting was investigated as a method to influence fluid movement on mineral or rock surfaces. The experimental setup was to pface a small drop of water containing an electrolyte on a solid surface directly or on the same solid surface coated with a hydrophobic film. The contact angle decreased with an applied electric field until it reached a saturation value associated with a critical voltage. The electrowetting experiments were conducted again after surfactant was added to the water drop. In all cases the contact angle decreased with increasing voltage and surfactant concentration. Electrowetting enhanced the wetting effect over that of the surfactant alone both by lowering the contact angle and by promoting rupture of the hydrophobic film. Four zones of behavior were identified based on the surfactant concentration and the voltage level. The results open the possibility that electrowetting can be used to enhance mobilization of one fluid relative to another in hydrocarbon recovery or contaminant remediation, as interfacial tensions control multiphase fluid flow.